Aplicación de biodiscos como sistema alternativo de tratamiento de lixiviados del relleno sanitario de Encarnación (Journal on studies and research of academic knowledge, 2019)
The present study has evaluated the behavior of a rotating contact biological reactor (Biodisc) to treat leachates, generated during the anaerobic decomposition of solid waste in the Encarnación sanitary landfill. The parameters analyzed were pH, conductivity, dissolved oxygen, total dissolved solids, turbidity, BOD5, COD, and nutrients. The hydraulic retention time was 20 days. The system presented high removal percentages of BOD5 with 96 %, tota nitrogen and ammonia in the order of 80 %, volatile solids 80 %, suspended solids 96 %. No significant reduction of other parameters was observed such as COD with 30 %, total phosphorus 44 %, fixed solids 30 % and total solids with 60 % removal. The results obtained reflect that the studied system is applicable as an alternative leachate treatment. However, it must be accompanied by other processes for nutrient removal and COD before final disposal in receptors agents.
Keywords: Biodiscs; Leached; Solid waste